PENGEMBANGAN KOMPETENSI APARATUR DI SEKRETARIAT DAERAH KABUPATEN MAHAKAM ULU - Roosilawati Arham Jonathan (Magister Administrasi Publik FISIP Universitas Mulawarman, 2017)
The purpose of this study was to describe and analyze the Competence Development Apparatus. The results of the research indicate that developing competence of apparatus in Mahakam Ulu District Secretariat, has brought changes increase the Competance of the apparatus. That indicates by some sub focus of the research that show there are increment competence, review by formal legality aspect it appear that development of apparatus competence can increase amount of educated civil servant such as bachelor’s degree and Master’s Degree. Less optimum of the developing competence program cause by the limited estimate allocated for developing of human resource specially for formal education and various of training. Various of awareness the employee in perceive the important of developing work ability through formal education and various of traning for the civil servant that can support the work continuity so the work result do not fulfill the qualification that expect .